Abnormal network homogeneity of default-mode network and its relationships with clinical symptoms in antipsychotic-naïve first-diagnosis schizophrenia - Kong, Mingjun; Chen, Tian; Gao, Shuzhan; Ni, Sulin; Ming, Yidan; Chai, Xintong; Ling, Chenxi; Xu, Xijia (Frontiers in Neuroscience, 2022)
Affecting around 0.5%-1% of the global population, schizophrenia is one of the severe mental disorders. A few studies have shown the functional disconnection in the default-mode network (DMN) of schizophrenia patients. However, the findings remain discrepant. In the current study, we explored the homogeneity of DMN in patients with schizophrenia and its relationships with symptom dimensions and cognition. Functional connectivity strength within the DMN, measured using resting-state functional magnetic resonance imaging, was compared between 57 first-episode drug-naive schizophrenia patients and 50 healthy controls. Network homogeneity and independent component analysis approaches were applied for statistical analysis. Our results showed that the NH values of patients were significantly higher in the left superior medial frontal gyrus and right cerebellum Crus Ⅰ and Ⅱ, while significantly lower in the right inferior temporal gyrus and bilateral posterior cingulate cortex compared to those in healthy controls. Support vector machine analysis showed that a combination of NH values in the left superior medial frontal gyrus, right cerebellum Crus Ⅰ, and right inferior temporal gyrus could distinguish schizophrenia patients from healthy subjects. Additionally, the negative correlation was observed between aberrant values of network homogeneity in the right cerebellum Crus Ⅰ and Ⅱ and PANSS global scores as well as social cognition scores in patients. We also observed negative correlations between the network homogeneity values in the left superior medial frontal gyrus and PANSS negative symptom scores, total scores, as well as values of NH in the right inferior temporal gyrus and the cognition dimensions, including speed of processing and social cognition. The results provided key data on the clinical features and brain images in schizophrenia, and further emphasized the vital role of DMN in the neuropathological mechanisms underlying schizophrenia.